Erythroid expansion and survival in response to acute anemia stress: The role of EPO receptor, GATA-1, Bcl-xL and caspase-3 - Aispuru, Gualberto Rodrigo (2008)
Erythropoietic stress occurs under conditions of tissular hypoxia, such as anemia. Functional relationships between erythroid bone marrow (BM) proliferation, differentiation, the expression of survival and apoptotic related proteins, as well as the features of the BM microenvironment upon acute anemic stress, are not fully elucidated. To achieve this aim, CF-1 Swiss mice were injected with a single dose of 5-fluorouracil (5-FU, 150 mg/kg ip) and a multiparametric analysis was conducted for 20 days. Apoptosis (TUNEL assay), BM architecture organization (scanning electronic microscopy), proliferation (DNA assay), differentiation (clonogenic cultures), expression of survival erythroid related proteins (EPO-R, GATA-1, Bcl-xL) as well as the expression of apoptotic- related proteins (Bax, activated Caspase-3) by Western blotting, were evaluated. Experimental data showed that apoptosis, arrest of cell proliferation and disruptions of BM architecture were maximal within the first period of acute stress (1-3 days). Bax and caspase-3 overexpressions were also coincident during this acute period. Moreover, from day 5 upon drug challenge BM responds to acute stress through the EPO-EPO-R system, prompting expressions of GATA-1 and Bcl-xL. Erythroid proliferation rates and red-cell-committed progenitors enhanced in a coordinated way to restore the size and function of the red cell compartment. A second overexpression wave of active caspase-3 was noticed during stress recovery. Together, these results indicate that in response to acute stress a dramatic increase in CFU-E (erythroid colony forming units) population is concomitant with upregulation of EPO-R, GATA-1 and Bcl-xL in the BM erythroid compartment, and that these concurrent processes are crucial for acquiring proper erythroid cell functionality without delayed response to tissular hypoxia. © 2008 International Federation for Cell Biology.